Critical sociology in the development of HOTS-oriented cognitive assessment instruments - Aris Martiana; Edi Istiyono; Widihastuti Widihastuti (Universitas Negeri Yogyakarta, 2022)
The current curriculum focuses on three domains, one of which is cognitive. Cognitive abilities are very important for the development of individual competencies so that instruments to measure them must be carried out. High quality cognitive instruments are needed in the assessment. Assessment with High Order Thinking Skills (HOTS) orientation as an effort to implement 6c, namely communication, collaboration, critical thinking, creative thinking, also computational logic and concern by developing cognitive instruments in Sociology scientific assessment. The method used is Research and Development which is focused on development. Cognitive instruments were compiled and carried out content validity from 4 experts for Sociology, Education and Law which were then tested on 93 students through a questionnaire in the form of google form. Analysis of the data used is by using software iteman 4.3. The results of this study are cognitive instruments with 15 HOTS questions in the form of multiple choice using content validity with Aiken's count obtained a score of 0.75 to 0.9375 so it is included in the medium and high categories. The instrument has an Alpha score of 0.558 so it is included in the reliable category. For items that have a difficulty level of 0.637, it means that the difficulty of the questions is moderate and the positive discriminatory power with a number of 0.243 is in the medium category. Then the distractor on the answer choices in the question items can function well because most of them are 0.05.